Finite time command filtered adaptive fault tolerant control for a class of uncertain nonlinear systems - Li, Yuan-Xin (Automatica (Oxford), 2019)
This paper studies the problem of finite time control for a class of uncertain nonlinear systems with unknown actuator faults where the total number of failures is allowed to be infinite. By fusing the techniques of command filter and backstepping control, a two-step design method is proposed to construct the controller, under which the effect of actuator faults can be compensated completely. Moreover, the proposed controller can avoid the “explosion of complexity” and “singularity” problems in the backstepping design framework. Based on the finite time stability criterion, it is proved that both the tracking performance and the closed-loop stability can be ensured in a finite time. Finally, a simulation example of one-link manipulator is given to verify the effectiveness the proposed finite fault tolerant control scheme.